Boxing participation by children and adolescents: A joint statement with the American Academy of Pediatrics - Purcell, Laura K (Pulsus Group Inc, 2012)
Thousands of boys and girls younger than 19 years of age participate in boxing in North America. Although boxing provides benefits for participants, including exercise, self-discipline and self-confidence, the sport of boxing encourages and rewards deliberate blows to the head and face. Participants in boxing are at risk of head, face and neck injuries, including chronic and even fatal neurological injuries. Concussions are one of the most common injuries occurring in boxing. Because of the risk of head and facial injuries, the Canadian Paediatric Society and the American Academy of Pediatrics vigorously oppose boxing as a sport for children and adolescents. These organizations recommend that physicians oppose boxing in youth and encourage patients to participate in alternative sports in which intentional head blows are not central to the sport.